The Divine Life of Sri Sri Sitaramdas Omkarnath, by C. Varadarajan, fourth edition. Kinkar Rameshananda (Calcutta), 2010, Rs. 100, 89 pages. - Petsche, Johana J.M. (International Journal for the Study of New Religions, 2014)
Book review